Bioaccumulation of heavy metals in Acanthopagrus latus collected from Al-Razazah Lake, middle of Iraq - Al-Najare, G.A.; Hantoush, A.A.; Al-Anber, L.J. M.; Al-Saad, H.T. (Iraqi Journal of Aquaculture, 2022)
Concentrations of cadmium, cobalt, cupper, iron, manganese and nickel were determined in four organs (liver, gills, ovaries and muscles) of Acanthopagrus latus, which belong to family of Sparidae collected from Al- Razazah Lake. Heavy metals have been determined by means of Atomic Absorption Spectrophotometry. The fish average weight was 378 g and the average length was 215 mm. Iron showed the highest value (1029.114 μg/g dry weight), while manganese showed the lower value (60.335 μg/g dry weight). This study showed that the concentration of heavy metals distributed in the organs was as follows: liver > gills > muscles > ovaries, while the total heavy metals concentration had been distributed as follow: iron > cupper > cadmium > nickel > manganese > cobalt.